Pengaruh Corporate Social Responsibility terhadap Agresivitas Pajak - Olga Vitaloka; R. Weddie Andriyanto; Yunia Amelia; A. Zubaidi Indra (Jurnal Akuntansi, Keuangan, dan Manajemen, 2023)
Purpose: This research aims to examine the effect of corporate social responsibility (CSR) on tax aggressiveness. Methodology: The type and source of data in this study is quantitative research, with data sources through the web of BUMN companies. The data used in this study are aggressiveness tax and CSR. sample determination using porposive sampling method and produce 35 samples of BUMN companies. The reason for using a BUMN company is because it is the biggest contributor in taxation. The analysis used in this study is multiple linear regression analysis using SPSS 26 software. Results: The results of the study show that CSR with a net fiscal income of more than 5% has an influence on tax aggressiveness. Meanwhile, CSR with a net fiscal income of less than 5% has no effect on tax aggressiveness Limitations: This research was only conducted by BUMN companies from 2015 to 2019. Contribution: This exploration has contributed to the enrichment of aspects of the financial accounting literature, particularly on the taxation of BUMN companies.